Comparison of Physiotherapeutic Intervention Programs on Handgrip Force and Myoelectric Activity in Individuals with COPD - Moura, Suenny Marrocos de Lima; Moura, Danilo de Macêdo; Gonçalves, Alessandra Feitosa; Silva, Maria Alessandra Sipriano da; Winkeler, Georgia Freire Paiva; Maciel, Simone dos Santos; Martins, Clarice Maria de Lucena; Santos, Heleodório Honorato dos (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Chronic obstructive pulmonary disease (COPD) modifies the electrical activity of accessory respiratory muscles, also leading to a marked peripheral muscular dysfunction, measured by the handgrip strength taken as an indicator of total body strength. Objective: To compare the effects of two different physiotherapeutic programs on handgrip strength and myoelectric activity in COPD patients. Methods: Participated in the study 17 individuals, randomly allocated into 2 groups: 1) Maneuvers: 62.7±15.4 years, 1.65±0.12 m, 81.4±18.2 kg, BMI: 29.9±5.0 kg/m2 ; 2) Threshold: 64.4±11.2 years, 1.58±0.08 m, 70.7±9.4 kg, BMI: 28.6±3.7 kg/m2 , diagnosed with COPD, submitted to surface electromyographic (sEMG) evaluation of sternocleidomatoid (SCM) and anterior scalene (AS), and handgrip strength, before and after the interventions. The data were analyzed with SPSS (20.0). Pared t-student and Wilcoxon tests were used to compare mean values of the handgrip strength and the Root Mean Square (RMS) of the sEMG signal (SCM and AS muscles), pre- and post-interventions. In addition, independent t-Student and Mann-Whitney tests were used to compare the RMS average of the sEMG signal between the right and left sides. Significant level was set at 5%. Results: When comparing pre and post-intervention values, there was a significant increase for the Threshold group handgrip strength (P=0.037). It was observed a sEMG activity of SCM and AS during dynamometry, vital capacity, forced vital capacity on inspiratory and expiratory pressure (P<0.05) for both analyzed groups. In the comparison of the myoelectric activity between the right and left sides for the SCM and AS, there was a significant difference in handgrip strength (P=0.009) and forced vital capacity (P=0.001) of the SCM muscle, post intervention for the Threshold group. Conclusion: The proposed physiotherapeutic programs improved the overall muscle strength for the Threshold group and the electromyographic activity of SCM and AS in the 2 groups.This study was registered in ReBEC: RBR-4VGP58